The essence of fundamental breach of contract: Exploring sales legislation in the Southeast European context - Drpljanin Vildan; Mašović-Muratović Irma (Univerzitetska Misao)
This paper examines the concept of the fundamental breach of contract and its application within the contract laws of Bosnia and Herzegovina, Croatia, Montenegro, North Macedonia, and Serbia, with a particular focus on sales contracts. It highlights the role of the United Nations Convention on Contracts for the International Sale of Goods (CISG) as a foundational framework for understanding fundamental breaches and their implications for international trade. While regional legislation does not explicitly reference the term "fundamental breach," this study demonstrates how the concept is implicitly recognized and addressed within national laws governing obligations. A comparative analysis of these legal systems reveals both similarities and divergences in the treatment of breaches, shedding light on shared practices and region-specific variations. Notably, although regional laws stress the importance of timely notification and define conditions for contract termination, they lack precise criteria for identifying fundamental breaches. This paper advocates for amendments to national civil codes to incorporate clearer definitions, aligning domestic legislation with international standards. Such reforms could enhance legal harmonization, strengthen adherence to modern international trade practices, and facilitate the integration of Southeast European countries into the global market.